Waqf-based Waste Management: A Proposed Model in Indonesia - Riani, Ririn; Fatoni, Ahlis (International Journal of Waqf, 2023)
Indonesia is now facing critical environmental problems, in addition to cases of growing waste, deforestation of scale such as air pollution, and lack of air supply and air services, raining down on Indonesia for some serious irregularities and deficiencies in environmental management. These serious issues must be addressed, and appropriate solutions must be implemented to reduce disaster risks and promote the growth of a better and more sustainable country. Since Islam is the main religion for the Indonesian people, an Islamic approach will be encouraged to solve this problem. Previous researchers requested that waqf is the most important Islamic legal entity that can be used for this purpose. Sustainable and integrated waste management or ISWM/Integrated Sustainable Waste Management focuses on waste management as a multi-actor. Waqf can contribute to long-term management that is used to manage and manage waste. Waqf institutions and others have pioneered some of these innovative schemes, but they have been massively implemented. So, this research will examine the concept of Waqf-Based Waste Management.